2018
DOI: 10.3390/pharmacy6010010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Dyslipidemia in Cardiovascular Disease Prevention: Focus on Old and New Drugs

Abstract: Prevention and treatment of dyslipidemia should be considered as an integral part of individual cardiovascular prevention interventions, which should be addressed primarily to those at higher risk who benefit most. To date, statins remain the first-choice therapy, as they have been shown to reduce the risk of major vascular events by lowering low-density lipoprotein cholesterol (LDL-C). However, due to adherence to statin therapy or statin resistance, many patients do not reach LDL-C target levels. Ezetimibe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 79 publications
0
61
0
1
Order By: Relevance
“…However, both agents may cause liver steatosis and are currently only in use as adjunct therapy in homozygous familial hypercholesterolemia 31,[238][239][240][241] . No data are available on cardiovascular outcomes with either lomitapide or mipomersen 242,243 .…”
Section: [H2] Inhibitors Of Vldl Productionmentioning
confidence: 99%
“…However, both agents may cause liver steatosis and are currently only in use as adjunct therapy in homozygous familial hypercholesterolemia 31,[238][239][240][241] . No data are available on cardiovascular outcomes with either lomitapide or mipomersen 242,243 .…”
Section: [H2] Inhibitors Of Vldl Productionmentioning
confidence: 99%
“…According to Akhani, et al [6] and Nnami, et al [7] clinical complications of atherosclerosis could be diminished and life prolonged if plasma lipid levels are lowered. It has also been found that long-term, effective treatment of hyperlipidemia can decrease the occurrence of ischemic heart disease [8]. But many promising agents developed have serious side effects, especially on adrenal function.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches are suggested to control dyslipidemia, including diet therapy and pharmacological interventions (Ahmed, Clasen, & Donnelly, 1998;Ito, 2012). However, taking synthetic lipid-lowering medications exerts some adverse effects and often its efficacy is attenuated after prolonged use (Ghaedi, Kord-Varkaneh, Mohammadi, Askarpour, & Miraghajani, 2019;Mohammadi, Hadi, Arab, Moradi, & Rouhani, 2019;Sahebkar et al, 2016;Zodda, Giammona, & Schifilliti, 2018). Considering the limitation of the lipidlowering drugs, there is a great deal of interest in nutraceuticals that may possibly complement the pharmaceutical treatments.…”
Section: Introductionmentioning
confidence: 99%